Pemeriksaan dan penyuluhan kesehatan pada masyarakat Desa Galuh Kabupaten Konawe - La Rangki; La Ode Alifariki; I Putu Sudayasa (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
High blood pressure, diabetes mellitus (DM), uric acid, and cholesterol are diseases that are getting longer but will definitely cause unbearable pain even cause death in patients. This community service aims to provide additional knowledge of risk factors, tackling non-communicable diseases and their complications. These community service activities include: conducting health checks and risk factors for hypertension (body weight, height, and body mass index / BMI) for screening for hypertension, gout and DM, health promotion in the form of health education. The incidence of dyslipidemia was 11.0% and the incidence of gout was 1.7%. The low results of screening or screening for disease risk factors is due to the first that the dominant activity participants are teenagers but after that after the age of the early elderly is as much as 33.3%, this has an impact on the high incidence of hypertension which is 32.9%.